The Malaysian Private Entity Reporting Standard (MPERS) Adoption and The Financial Reporting Quality: Evidence From Small and Medium Enterprises (SMES) in Malaysia - Siti Nur Ayuni Rosli; Nurul Nazlia Jamil; Ainulashikin Marzuki (Human Resource Management Academic Research Society, 2024)
Indexed by ERA